Some features of commercial Law in Vietnam - Cương, Ngô Huy (VNU Journal of Science: Legal Studies; Vol 27 No 4, 2011)
Abstract. The article introduces and analyses some features of the current commercial law branch in Vietnam in order to facilitate researches on it. The principal features of Vietnamese commercial laws in general and in its concrete institutions can be found in this article.